2018
DOI: 10.1016/s2352-3018(18)30175-9
|View full text |Cite
|
Sign up to set email alerts
|

All-cause mortality among people with HIV released from an integrated system of jails and prisons in Connecticut, USA, 2007–14: a retrospective observational cohort study

Abstract: US National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Unlike previous studies [ 20 , 56 ], IDU transmission risk and high psychiatric need correlated with VS over time. While IDU and psychiatric need were not associated with frequency of transitional case management utilization, such individuals may have received additional psychiatric case management to link and retain them in treatment for psychiatric or substance use disorders, which could have improved VS. Also, some PLWH with an IDU history died early during follow-up, including from drug overdose [ 66 ], which limited our ability to clearly assess the role of current or past IDU on longitudinal HIV treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies [ 20 , 56 ], IDU transmission risk and high psychiatric need correlated with VS over time. While IDU and psychiatric need were not associated with frequency of transitional case management utilization, such individuals may have received additional psychiatric case management to link and retain them in treatment for psychiatric or substance use disorders, which could have improved VS. Also, some PLWH with an IDU history died early during follow-up, including from drug overdose [ 66 ], which limited our ability to clearly assess the role of current or past IDU on longitudinal HIV treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For those treated in correctional facilities, viral suppression on ART is generally observed, sometimes surpassing those in the non-incarcerated population. Nevertheless, virological suppression is often not sustained after release [3,7,18,19,21], mortality is high [6,22] and retention in care is poor [17,[23][24][25].…”
Section: Poor Retention In Care and Lost Benefits After Release An Omentioning
confidence: 99%
“…It has been shown that poor retention in HIV care predicts poor survival [30,31], thus, it is unsurprising to find a poor retention, and a high rate of mortality among former HIV-infected [6,22].…”
Section: Factors Associated With Return To Hiv Carementioning
confidence: 99%
“…Release from prison carries a very high risk of death due to overdose [ 15 , 16 ], particularly among people living with HIV [ 12 , 15 , 17 ]. Given the generally low levels of methadone uptake in Kyrgyz prisons as well as the increased risks surrounding release, we deployed a screening, brief intervention, and referral to treatment (SBIRT) strategy to increase methadone program participation among incarcerated people with OUD who were scheduled to be released from prison within six months.…”
Section: Introductionmentioning
confidence: 99%